TREATMENT OF BRONCHOPULMONARY PATHOLOGY IN CHILDREN WITH CYSTIC FIBROSIS IN THE ARAL SEA REGION (Multidisciplinary Journal of Science and Technology, 2025)
In recent years, the hereditary disease cystic fibrosis has been increasingly diagnosed in children with an autosomal recessive type of inheritance, caused by a pathogenic variant of the nucleotide sequence (mutation) of the gene of the cystic fibrosis transmembrane conductance regulator (CFTR). According to experts from the World Health Organization (WHO), "... 45-50 thousand children with cystic fibrosis are born in the world every year, and the number of heterozygous carriers of the disease is tens of millions ..." "... The first symptoms appear in 65% of children under six months, 80% under one year and 90% under two years..." Today, the increase in the incidence rate, insufficient study of the pathogenetic mechanisms, the features of the clinical course, the occurrence of severe complications of cystic fibrosis require scientific research on this nosology.